The sens of reality: Studies in Ideas and their History - Berlin, Isaiah (London Pimlico, 1996)
Isaiah Berlin's The Sense of Reality contains an important body of previously unknown work by one of our century's leading historians of ideas, and one of the finest essayists writing in English. Eight of the nine pieces included here are published for the first time, and their range is characteristically wide: the subjects explored include realism in history; judgement in politics; the history of socialism; the nature and impact of Marxism; the radical cultural revolution instigated by the Romantics; Russian notions of artistic commitment; and the origins and practice of nationalism. The title essay, starting from the impossibility of historians being able to recreate a bygone epoch, is a superb centerpiece.